2001
DOI: 10.1086/320944
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Dissipation in the Interstellar Medium: The Coexistence of Forced and Decaying Regimes and Implications for Galaxy Formation and Evolution

Abstract: We discuss the dissipation of turbulent kinetic energy in the global interstellar medium (ISM) by E k means of two-dimensional, MHD, nonisothermal simulations in the presence of model radiative heating and cooling. We argue that dissipation in two dimensions is representative of that in three dimensions as long as it is dominated by shocks rather than by a turbulent cascade. Contrary to previous treatments of dissipation in the ISM, this work considers realistic, stellar-like forcing : energy is injected at a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…An alternative to the present modelling is to consider the ISM as turbulent. As shown by Avila‐Reese & Vazquez‐Semadeni (2001), the ISM can be considered as a globally turbulent medium, with turbulence forced in specific places (the star‐forming regions) and propagating throughout the volume. The ‘diffusion’ velocity of turbulence is connected to the time‐scale of decay of turbulence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative to the present modelling is to consider the ISM as turbulent. As shown by Avila‐Reese & Vazquez‐Semadeni (2001), the ISM can be considered as a globally turbulent medium, with turbulence forced in specific places (the star‐forming regions) and propagating throughout the volume. The ‘diffusion’ velocity of turbulence is connected to the time‐scale of decay of turbulence.…”
Section: Discussionmentioning
confidence: 99%
“…This picture is challenged by the results of many simulation programs, aimed at the numerical modelling of the ISM (see, for example, Mac Low et al 1998; Ostriker, Gammie & Stone 1999; Avila‐Reese & Vazquez‐Semadeni 2001; Kritsuk & Norman 2002; see Mac Low 2002 and Vazquez‐Semadeni 2002 for reviews). In this context, the ISM is dominated by compressible, supersonic, MHD turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…A major discovery of simulations is that supersonic MHD turbulence decays in roughly a crossing time (based on the rms turbulent velocity) regardless of magnetic effects and the discreteness of energy injection (Mac Low et al 1998;Stone, Ostriker & Gammie 1998;Mac Low 1999;Avila-Reese & Vázquez-Semadeni 2001;Ostriker et al 2001). Decay is faster with cooling (Kritsuk & Norman 2002b, Pavlovski et al 2002 because the average Mach number is larger.…”
Section: Decay Of Supersonic Mhd Turbulencementioning
confidence: 99%
“…We will use γ in = σ z /v w . For the turbulence decay, several numerical studies have demonstrated that supersonic turbulence dissipates rapidly, in a timescale roughly equivalent to the crossing time for the driving scale at the turbulence velocity (e.g., Mac Low 1999;Stone et al 1999;Avila-Reese & Vázquez-Semadeni 2001). The latter authors have found values of t d ≈ 15 − 20 Myr for ISM properties typical of the MW.…”
Section: 5mentioning
confidence: 99%